Hepatitis B Virus Protein X-induced Expression of the CXC Chemokine IP-10 Is Mediated through Activation of NF-κB and Increases Migration of Leukocytes - Zhou, Yu (American Society for Biochemistry and Molecular Biology, 2010)
Interferon-γ inducible protein 10 (IP-10) involves inflammatory cell recruitment and cellular immune damage during virus infection. Although an increase of the peripheral IP-10 level is known in HBV-infected patients, the molecular basis of HBV infection inducing IP-10 expression has remained elusive. In the present study, we demonstrate that hepatitis B virus protein X (HBx) increases IP-10 expression in a dose-dependent manner. Transfection of the HBx-expressing vector into HepG2 cells results in nuclear translocation of NF-κB, which directly binds the promoter of IP-10 at positions from −122 to −113, thus facilitating transcription. The addition of the NF-κB inhibitor blocks the effect of HBx on IP-10 induction. In parallel, increase of NF-κB subunits p65 and p50 in HepG2 cells also augments IP-10 expression. Furthermore, we show that HBx induces activation of NF-κB through the TRAF2/TAK1 signaling pathway, leading to up-regulation of IP-10 expression. As a consequence, up-regulation of IP-10 may mediate the migration of peripheral blood leukocytes in a NF-κB-dependent manner. In conclusion, we report a novel molecular mechanism of HBV infection inducing IP-10 expression, which involves viral protein HBx affecting NF-κB pathway, leading to transactivation of the IP-10 promoter. Our study provides insight into the migration of leukocytes in response to HBV infection, thus causing immune pathological injury of liver.